1994
DOI: 10.1007/bf02257783
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant preoperative radiotherapy for locally advanced rectal carcinoma

Abstract: Although there is no statistically significant survival benefit in the whole series, there is a survival benefit for the subset of patients considered by the surgeon to have undergone a curative operation. We recommend that this form of adjuvant therapy should be offered to all patients with locally advanced rectal cancer who are to undergo radical surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
1
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(99 citation statements)
references
References 35 publications
0
90
1
8
Order By: Relevance
“…30 To our knowledge, there have been no reports to date of complete tumor regression occurring when surgery is performed within 1 week after the end of radiotherapy, a finding that is consistent with our own data. 10,12,14,16,17,19 In contrast, in studies with a longer interval between the end of radiotherapy and surgery (Ͼ 10 days), complete histologic regression was reported in 2-11% of the patients. 7,30,38 -41 However, to diagnose complete tumor regression, the entire tumor region must be sampled and carefully screened for any small surviving foci of carcinoma by thorough histologic workup.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…30 To our knowledge, there have been no reports to date of complete tumor regression occurring when surgery is performed within 1 week after the end of radiotherapy, a finding that is consistent with our own data. 10,12,14,16,17,19 In contrast, in studies with a longer interval between the end of radiotherapy and surgery (Ͼ 10 days), complete histologic regression was reported in 2-11% of the patients. 7,30,38 -41 However, to diagnose complete tumor regression, the entire tumor region must be sampled and carefully screened for any small surviving foci of carcinoma by thorough histologic workup.…”
Section: Discussionmentioning
confidence: 96%
“…In the literature data, a reduced number of lymph node metastases after preoperative radiotherapy was reported in some studies 8,16,18,38,42,44 whereas in other studies no significant difference was found. 12,17,32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of preoperative radiotherapy is to sterilize the resection margins and to destroy microscopic collections of cancer cells situated outside the mesorectum, in presacral lymph nodes and at lateral pelvic walls, a potential focus of local recurrence and, a source of distant metastasis. Previous studies using a high dose radiation with variable fraction schedules have demonstrated a significant reduction in local recurrence compared with surgery alone (3)(4)(5). However, a significant number of patients suffer from local recurrence and distant metastasis even after multi-modality therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: rectal neoplasm staging; endosonography; magnetic resonance imaging; comparative study; cost -benefit analysis; rectal neoplasms therapy; radiotherapy; surgery; pathology Meticulous surgical technique, as exemplified by total mesorectal excision (TME), has improved survival by reducing local recurrences in patients undergoing resection with curative intent (Heald, 1995;Carlsen et al, 1998). In addition, preoperative neoadjuvant radiotherapy and chemoradiotherapy regimens also promise to improve survival (Marsh et al, 1994;Anonymous, 1997;Pahlman et al, 1998;Dahlberg et al, 1999), but their success needs to be tempered against the inevitable morbidity associated with such treatments (Dahlberg et al, 1998). In 1997, the Scandinavian rectal cancer trials (Anonymous, 1997) showed that preoperative therapy reduced local recurrence rates in patients undergoing rectal cancer surgery.…”
mentioning
confidence: 99%